1998
DOI: 10.1152/ajpendo.1998.274.5.e808
|View full text |Cite
|
Sign up to set email alerts
|

Dual-energy X-ray absorptiometry: fat estimation errors due to variation in soft tissue hydration

Abstract: Dual-energy X-ray absorptiometry (DXA) is rapidly gaining acceptance as a reference method for analyzing body composition. An important and unresolved concern is whether and to what extent variation in soft tissue hydration causes errors in DXA fat estimates. The present study aim was to develop and validate a DXA physical hydration model and then to apply this model by simulating errors arising from hypothetical overhydration states. The DXA physical hydration model was developed by first linking biological s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
137
2
5

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(147 citation statements)
references
References 26 publications
3
137
2
5
Order By: Relevance
“…Other studies point to an important role for tissue hydration in the error in estimates of fat content by DXA. 23,30 In particular, Fusch et al 23 found that tissue hydration declined as a function of increasing body mass in their experimental subjects, and this decrease in hydration was linked to an increasing underestimate of the fat content of the animals. Although Going et al 31 manipulated hydration status and found no effect on fat content by DXA, in a sample of 19 adults, the extent of their manipulations (less than 2%) was small relative to the individual variability in tissue hydration, and in the range where our own in vitro manipulations detected no effect (Figure 3b).…”
Section: Discussionmentioning
confidence: 98%
“…Other studies point to an important role for tissue hydration in the error in estimates of fat content by DXA. 23,30 In particular, Fusch et al 23 found that tissue hydration declined as a function of increasing body mass in their experimental subjects, and this decrease in hydration was linked to an increasing underestimate of the fat content of the animals. Although Going et al 31 manipulated hydration status and found no effect on fat content by DXA, in a sample of 19 adults, the extent of their manipulations (less than 2%) was small relative to the individual variability in tissue hydration, and in the range where our own in vitro manipulations detected no effect (Figure 3b).…”
Section: Discussionmentioning
confidence: 98%
“…FFM hydration was not significantly correlated (R 2 = 0.157: P = 0.16) with 4C/DXA %BF differences in our obese subjects. van der Ploeg et al regarded the lack of association between variation in FFM hydration and %BF error as understandable given the theoretical calculations of Pietrobelli et al (20). The latter determined that hydration changes of 1-5% would only lead to small DXA errors (<1%).…”
Section: Discussionmentioning
confidence: 99%
“…DXA has been validated against various multicompartment models in young (Prior et al, 1997;Clasey et al, 1999), old (Clasey et al, 1999) and a wide age range of healthy sedentary individuals (Gallagher et al, 2000). Nevertheless, the validity of the method has remained subject to question, particularly with regard to concerns over tissue thickness and hydration levels (Laskey et al, 1992;Jebb et al, 1995;Pietrobelli et al, 1996Pietrobelli et al, , 1998Wang et al, 1998;van der Ploeg et al, 2003), which will vary between individuals and groups of subjects.…”
Section: Introductionmentioning
confidence: 99%